Accuracy of Cuff-Measured Blood Pressure: Systematic Reviews and Meta-Analyses - Picone, Dean S.; Schultz, Martin G.; Otahal, Petr; Aakhus, Svend; Al-Jumaily, Ahmed M.; Black, J. Andrew; Bos, Willem J.; Chambers, John B.; Chen, Chen-Huan; Cheng, Hao-Min; Cremer, Antoine; Davies, Justin E.; et al. (Journal of the American College of Cardiology, 2017)
Hypertension (HTN) is the single greatest cardiovascular risk factor worldwide. HTN management is usually guided by brachial cuff blood pressure (BP), but questions have been raised regarding accuracy.This comprehensive analysis determined the accuracy of cuff BP and the consequent effect on BP classification compared with intra-arterial BP reference standards.Three individual participant data meta-analyses were conducted among studies (from the 1950s to 2016) that measured intra-arterial aortic BP, intra-arterial brachial BP, and cuff BP.A total of 74 studies with 3,073 participants were included. Intra-arterial brachial systolic blood pressure (SBP) was higher than aortic values (8.0 mm Hg; 95% confidence interval [CI]: 5.9 to 10.1 mm Hg; p < 0.0001) and intra-arterial brachial diastolic BP was lower than aortic values (-1.0 mm Hg; 95% CI: -2.0 to -0.1 mm Hg; p = 0.038). Cuff BP underestimated intra-arterial brachial SBP (-5.7 mm Hg; 95% CI: -8.0 to -3.5 mm Hg; p < 0.0001) but overestimated intra-arterial diastolic BP (5.5 mm Hg; 95% CI: 3.5 to 7.5 mm Hg; p < 0.0001). Cuff and intra-arterial aortic SBP showed a small mean difference (0.3 mm Hg; 95% CI: -1.5 to 2.1 mm Hg; p = 0.77) but poor agreement (mean absolute difference 8.0 mm Hg; 95% CI: 7.1 to 8.9 mm Hg). Concordance between BP classification using the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure cuff BP (normal, pre-HTN, and HTN stages 1 and 2) compared with intra-arterial brachial BP was 60%, 50%, 53%, and 80%, and using intra-arterial aortic BP was 79%, 57%, 52%, and 76%, respectively. Using revised intra-arterial thresholds based on cuff BP percentile rank, concordance between BP classification using cuff BP compared with intra-arterial brachial BP was 71%, 66%, 52%, and 76%, and using intra-arterial aortic BP was 74%, 61%, 56%, and 65%, respectively.Cuff BP has variable accuracy for measuring either brachial or aortic intra-arterial BP, and this adversely influences correct BP classification. These findings indicate that stronger accuracy standards for BP devices may improve cardiovascular risk management.
EVALuna2:3961